2017
DOI: 10.3390/biomedicines5020029
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB Signalling in Glioblastoma

Abstract: Nuclear factor-κB (NF-κB) is a transcription factor regulating a wide array of genes mediating numerous cellular processes such as proliferation, differentiation, motility and survival, to name a few. Aberrant activation of NF-κB is a frequent event in numerous cancers, including glioblastoma, the most common and lethal form of brain tumours of glial cell origin (collectively termed gliomas). Glioblastoma is characterized by high cellular heterogeneity, resistance to therapy and almost inevitable recurrence af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(56 citation statements)
references
References 118 publications
(201 reference statements)
0
56
0
Order By: Relevance
“…Analyses of the in vitro effects of PBI-05204 indicate that they were mainly cytotoxic with induction of apoptosis which was shown by increased Annexin V staining of cells and activation of capsase 3. Additionally, PBI-05204 was able to reduce NF-kB expression, commonly associated with elevated inflammation and molecules associated with resistance to radiotherapy, chemotherapy, and relative stemness of GBM (Gray et al, 2014;Soubannier and Stifani, 2017;Kaltschmidt et al, 2019). Anti-angiogenesis was also evident and may be due in part to the ability of oleandrin to inhibit FGF-2 export (Smith et al, 2001;Manna et al, 2006).…”
Section: Discussionmentioning
confidence: 97%
“…Analyses of the in vitro effects of PBI-05204 indicate that they were mainly cytotoxic with induction of apoptosis which was shown by increased Annexin V staining of cells and activation of capsase 3. Additionally, PBI-05204 was able to reduce NF-kB expression, commonly associated with elevated inflammation and molecules associated with resistance to radiotherapy, chemotherapy, and relative stemness of GBM (Gray et al, 2014;Soubannier and Stifani, 2017;Kaltschmidt et al, 2019). Anti-angiogenesis was also evident and may be due in part to the ability of oleandrin to inhibit FGF-2 export (Smith et al, 2001;Manna et al, 2006).…”
Section: Discussionmentioning
confidence: 97%
“…NF-κB extensively participates in numerous cellular processes such as differentiation, proliferation, survival, and motility through regulating a wide array of gene expressions [30]. In response to a variety of stimuli in the growth of glioblastomas, NF-κB can be emergently activated for migration, invasion, chemoresistance, resistance to radiotherapy, GBM stemness, and mesenchymal identity [31]. Terzuoli et al demonstrated involvement of the bradykinin-NF-κB axis in angiogenesis and inflammatory responses in human endothelial cells [32].…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB, as an important transcription factor, is involved in various cellular processes, including migration, proliferation, and survival. Inflammatory cytokines, PAMP and DAMP, could trigger further pro-NF-κB signaling throughout the activation of TNFRs and TLRs [53][54][55][56]. The deregulated activity of NF-κB is becoming an indicator of most neoplasm processes, including GBM.…”
Section: Progression Of Gbmmentioning
confidence: 99%